PEWARNAAN GRAM ISOLAT BAKTERI DARI LIMBAH BIOMEDIS CAIR RUMAH SAKIT UNHAS DENGAN METODE ZIEHL NEELSEN - Wulandhani, Suci; Wahyuni, Ayu; Hasyim, Ahmad; Misnarliah (Universitas Cokroaminoto Palopo, 2024)
Hospitals as one of the health service institutions that provide inpatient, outpatient and emergency services, in their implementation can produce waste in solid, liquid or gas form which can pollute the environment. Hospital waste water is an accumulation of domestic waste and liquid biomedical waste with high levels of organic pollutants, so it can be treated biologically. Liquid biomedical waste contains many microorganisms where the presence of microorganisms, in this case bacteria, can be used as an indicator of waste management and unfavorable environmental conditions. One waste water treatment technology that is safe for the environment is using bacteria that have the potential to act as decomposers in the biodegradation process. To obtain bacteria that have the potential to act as natural decomposers, you can isolate the waste itself. The bacteria found in liquid biomedical waste make it possible to find a group of non-pathogenic hydrolytic bacteria where this group of bacteria can produce various enzymes that are capable of degrading liquid biomedical waste. Gram staining is a method to differentiate between types or spesies of bacteria namely gram-positive bacteria and gram-negative bacteria. The aim of this study was to identify bacteria using Ziehl Neelsen gram staining. The results of the research showed that there were two bacterial isolates that were gram negative, namely isolate codes UH1.1 and UH1.2 (bacillus) form characterized by the appearance of brick red cells and five isolates that were gram positive, namely isolate codes UH1.3, UH2.1 (bacillus) UH2.2, UH2.3 and UH3.1 (coccus form) are characterized by the appearance of purple cells, the difference in color is due to differences in the composition of the cell walls of each bacteria.